2‐Sulfanylhydroquinone Dimer as a Switchable Fluorescent Dye. Issue 62 (2nd October 2019) - Kamimura, Akio; Sakamoto, Sanshiro; Umemoto, Haruka; Kawamoto, Takuji; Sumimoto, Michinori
Abstract: A new dye was developed, the photoluminescence properties of which are controlled by a chemical reaction. The fluorescence properties of 2‐sulfanylhydroquinone dimers depend on the number of hydroxyl groups that are acylated. Unprotected or monoacylated 2‐sulfanylhydroquinone dimers displayed good fluorescence properties, whereas diacylated and tetraacylated 2‐sulfanylhydroquinone dimers showed dramatically decreased fluorescence. A monomesylated derivative was devised, which shows good fluorescence characteristics as a switching fluorescence dye through a chemical reaction. Abstract : Blue fluorescence on/off ! A new fluorescent dye, a monomesylated 2‐sulfanylhydroquinone dimer, was developed. The dye emits blue light upon irradiation with UV light, whereas its acyl derivatives are inert towards photoluminescence activity. Hydrolysis of the derivatives restores the photoluminescence and blue‐light emission upon irradiation with UV light.